Investigating the structural and functional effects of naturally occurring single nucleotide polymorphisms in hGSTP1-1 - Makeleni, Nelisa (My University, 2018)
SNPs are DNA sequence variations occurring when a nucleotide in the genome differs between members of a species. These are the most frequent types of genetic variations, accounting for about 90 % of the genetic variations in humans. Some changes in coding regions of DNA tend to alter the amino acid sequence and therefore affect the produced protein. The human glutathione S-transferase class pi (hGSTP1-1) has been studied for its involvement in a broad range of functions such as detoxification. It has recently drawn interest because of its increased levels in tumours. In order to incorporate mutations into the hGSTP1-1 DNA sequence, site directed mutagenesis was performed to obtain the SNP forms and their effect on the structure, stability and function were studied. The activity was measured using the 1-chloro-2,4dinitrobenzene (CDNB-GSH) enzyme assay. The SNP forms L159M, located in the hydrophobic core of domain 2, and T110S positioned next to the H-site of the protein did not affect the secondary structure when compared to the wild-type, while the L159M SNP form had an effect on the protein’s tertiary structure when determined using CD and fluorometer. Both of the SNP forms showed a difference in the exposure of hydrophobic surfaces as indicated by ANS binding studies. The SNPs had no effect on the thermal stability of the protein although the enzyme activity of SNP L159M and the SNP T110S is decreased by about 57% and 18 %, respectively, when compared with the activity of the wild-type. The SNP T110S does not have a significant effect on the structure and activity of hGSTP1-1 while the L159M showed significant changes suggesting possible effects on both the structure and activity. This may be attributed to its location in a conserved hydrophobic core of domain 2 of hGSTP1-1. The decrease in activity of the L159M hGSTP1-1 may have a negative role on the detoxification function of the protein.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, February 2018